Problematizing Contemporary Islamic Discourse: A Conceptual Modeling of New Heroes in Indonesian Islamic Biographical Films - Mochamad Andhy Nurmansyah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2023)
PurposeThis study problematizes the interconnectedness between religion and media once again within the context of Indonesian biopics. This paper looks at the pattern of transformation of two Islamic elite-authoritative figures into Islamic-popular heroes that are thematically intertwined with Islamic discourse in Indonesia’s reform era. MethodThe research in this article combines several theoretical concepts by examining the relationship between text and context. The social semiotic paradigm of Kress becomes the main theory for disecting the text, while the concept of cultural commodities from Fiske and discourse formation from Foucault become the frame of reference for viewing the relationship between text and context. Results/findingsThe binary modes in those two biopics are not identical, according to this article, but both have transformed the stable concept of historical figures into more complex ones that generate polysemic ideas from an ideological standpoint. This article also explains how the process of meaning formation in the film's two Islamic figures are affected by three entities forming a three-party dialectic model. ConclusionIn the case of two biopics, Sang Pencerah (2010) and Sang Kiai (2013), this article confirms a dynamic model of conceptual design that connects texts and context. It demonstrates the existence of some variables that contribute to the polarization of contemporary Islam discourses in Indonesia.